Orthopedic surgery residents' perception of online education in their programs during the COVID-19 pandemic: should it be maintained after the crisis? - Figueroa, Francisco; Figueroa, David; Calvo-Mena, Rafael; Narvaez, Felipe; Medina, Natalia; Prieto, Juan (Acta orthopaedica, 2020)
Background and purpose - During the COVID-19 pandemic, most of the teaching centers in Chile have shifted to online resources. We decided to do a survey on orthopedic residents regarding this type of education to assess for strengths and weaknesses of digital education in orthopedic programs. Methods - A survey was performed targeting 110 orthopedic residents belonging to different training programs around the country. 100 residents completed the survey. Results - 86% stated that their programs are using online education. When asked in detail, 86% had been involved in webinars, 28% had received online presentations, 12% had participated in online tests, and 7% had evaluated patients. Webinars were rated (1 = very unsatisfactory, 10 = very satisfactory) with a mean grade of 8.1 (1-10), online presentations 7.3 (1-10), online tests 3.8 (1-8), and online patient evaluations 2.9 (1-9). When asked if, after the end of the pandemic, they would continue using the online modalities, 82% would continue attending webinars, 72% would continue watching online presentations, 27% would continue performing online tests, and 33% of the residents would continue performing online evaluations of patients. Interpretation - Even though resident evaluation of online activities is positive, face-to-face theoretical activities are still valued as a necessary complement for orthopedic residency education.